Pengaruh Berbagai Jenis Media Dan Lama Penyimpanan Benih Terhadap Viabilitas Dan Vigor Benih Kakao (Theobroma cacao L.) - Agus Ardi; Abdul Rahman; Syahbudin Hasibuan (Universitas Medan Area, 2021)
Effect of Various Types of Media and Duration of Storage of Seeds on Viability and Vigor of Cocoa (Theobroma cacao L.) Seeds. The method used in this research is the Factorial Completely Randomized Design (CRD) method, which consists of 2 treatment factors, Factor I, namely storage media with 4 treatment levels, namely: M0 without storage media; M1 = use of PE plastic; M2 = use of aluminum foil; M3 = use of gunny sacks; M4 = using a glass bottle. each treatment was repeated 2 (two) times. The second factor is storage time with 3 levels of treatment, namely: W1 = stored for 1 (one) week; W2 = stored for 2 (two) weeks; W3 = stored for 3 (three) weeks. The parameters observed in this study were viability and vigor. seed growth rate (%). Simultaneous growth of seeds (%), potential for seed growth (%), germination of seeds (%).From the research results can be concluded as follows:1.) the use of various types of seed storage media (M0) (without treatment), M1 (PE plastic), M2 (aluminum paper), M3 (gunny sacks), and M4 (glass bottles) are treatments that give no real results at age. 1-3 days after planting and the yields were very real at the age of 4-7 days after planting on the speed of seed growth, gave no real results at the age of 1-4 dast and the results were very real at the age of 5-7 days against the synchronization of seed growth, giving no real results at age 3 days after planting and was very significant at the age of 4-5 days after planting on the potential for seed growth, and gave very real results on the germination capacity of seeds. 2. The duration of 1 week of storage (M1) has a very significant effect on all parameters, namely the speed of seed growth, simultaneous growth of seeds, potential for seed growth and germination, while the storage time is 2 minutes (M2) and storage time is 3 minutes (M3). ), has no significant effect on all observed parameters, 3. The interaction of the two treatment factors has a very significant effect on all parameters, namely the speed of seed growth, synchronization of seed growth, potential for seed growth and germination